METODE BARU MEMAHAMI ALQURAN DALAM PERSPEKTIF SHAHRUR - Amri, Yaser (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2014)
Raised in Syria and educated in Moscow, Shahrur's intellectual profileinfluenced by the Syrian political situation of his era as well as Marxism.Having been studied linguistic and philosophical positivism that can betraced from Bertrand Russell and Alfred Whitehead to Kant, Fichte andHegel, Shahrur believes that Islamic teachings can be reconciled withmodern rational experiences of reality. Proposing the theory of limit hetried to reinterprate Islamic concept of hudud and a better understandingof the sacred book through Hermeneutics.